Takhrij and Syarah Hadith of Agrotechnology Al-Habbah As-Sauda for Disease Prevention - Rifaldi Ridha Akhira; Wahyudin Darmalaksana; Muhammad Subandi (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet about black cumin plants. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study is that black cumin does not only function to heal but contains elements that support the human immune system. The conclusion of this study is the takhrij and syarah of the Prophet's traditions regarding black cumin plant as herbal medicine which can be recognized as an antidote for several diseases because it has many benefits and properties contained in it.